TRIB3-EGFR interaction promotes lung cancer progression and defines a therapeutic target - Jiao-jiao Yu (Nature Portfolio, 2020)
Depletion of tribbles pseudokinase 3 (TRIB3) is known to suppress the expression of several tumor-promoting factors, including EGFR. Here, the authors show that TRIB3 interacts with EGFR and regulates its stability and activity, and perturbing EGFR-TRIB3 interaction attenuates NSCLC progression by accelerating EGFR degradation.